Severe hydronephrosis secondary to uterine artery pseudoaneurysm in the early second trimester of pregnancy: A case report - Tsukuru Amano; Shinsuke Tokoro; Shunichiro Tsuji; Takashi Inoue; Fuminori Kimura; Takashi Murakami (BMC, 2017)
Abstract Background Uterine artery pseudoaneurysm (UAP) normally presents genital bleeding in the puerperal period, and severe hydronephrosis rarely presents during pregnancy. We report a rare case of severe ureteral obstruction accompanied by uterine artery pseudoaneurysm in the early second trimester of pregnancy, which was successfully treated by surgical intervention. Case presentation A 42-year-old nulligravid woman who had undergone myomectomy 3 years earlier was referred to our hospital for acute left abdominal pain at the 17th week of gestation. Ultrasonography showed severe left hydronephrosis and a 6-cm mass in the parauterine space. Color Doppler ultrasonography revealed a spinning turbulent flow pattern inside the mass lesion. Contrast-enhanced computed tomography revealed the left uterine artery feeding blood flow to the mass and left ureteral obstruction by the mass. These results indicated left hydronephrosis secondary to left uterine artery pseudoaneurysm. To resolve the problem, laparotomy was performed. As uterine artery isolation was impossible, ligation of the left internal iliac artery and releasing of the ureteral obstruction were carried out. The hydronephrosis and abdominal pain promptly resolved after the surgery. Thereafter, fetal development proceeded normally in the remaining months of the pregnancy. A healthy baby was delivered through cesarean section at 36 weeks gestational age. At the cesarean section, the left lower uterine segment where the UAP had been present was not visible because of the firm adhesion in around it. Conclusions Uterine artery pseudoaneurysm can cause hydronephrosis in the early second trimester of pregnancy. Ligation of the unilateral internal iliac artery is a safe and effective intervention to block the blood flow to the uterine artery pseudoaneurysm during pregnancy, when uterine artery ligation seems not possible. In the pregnancy after previous surgical procedures to the uterus, uterine artery pseudoaneurysm should be considered in the differential diagnosis of symptomatic hydronephrosis.